PENGARUH BEBAN KERJA TERHADAP KEPUASAN KERJA DENGAN WORK-LIFE BALANCE SEBAGAI VARIABEL INTERVENING PADA PT. BANK RAKYAT INDONESIA (PERSERO) TBK. CABANG JAMBI - Syamsasni, Anggun; Amin, Shofia; Setiawan, Wahyu Juari (Journal of Business Studies and Management Review, 2025)
AbstractThis study aims to analyse the effect of workload on job satisfaction with work-life balance asan intervening variable at PT Bank Rakyat Indonesia (Persero) Tbk. Jambi Branch. Thisresearch uses quantitative methods with data collection techniques by distributingquestionnaires to 77 respondents. Hypothesis testing using descriptive analysis techniquesusing the SmartPLS tool. The results of this study indicate that (1) workload has a positive andsignificant effect on job satisfaction. (2) Workload has a significant effect on work-life balance.(3) Work-life balance has a positive and significant effect on job satisfaction. (4) Workload hasa significant effect on job satisfaction through work-life balance as an intervening variable.Keywords: Job Satisfaction, Workload, Work-life balance